Analysis of The Preparation and Implementation of Learning Implementation Plan Curriculum 2013 on Jurisprudence Subjects - Ahmad Khalakul Khairi; Mohd Arif Nazri; Tuti Alawiah (IJECA (International Journal of Education and Curriculum Application), 2020)
The aims of this research to determine the preparation and implementation of Learning Implementation Plan Curriculum 2013 on Jurisprudence Subjects. This research is a descriptive qualitative research. This research was conducted on Jurisprudence teachers in grades V and VI. Data collection techniques using interviews, observation, and documentation. Examination of the validity of the data in this study used triangulation of sources, while the data analysis technique used the following steps: data reduction, data presentation and conclusion drawing. The results showed that: a) The preparation of learning implementation plan curriculum 2013 for the V and VI class of Islamic Elementary School (MI) was not fully in accordance with the curriculum 2013 demands. b) The implementation of learning implementation plan curriculum  for the V and VI grade was still not fully appropriate with the principle of implementing the curriculum 2013. c) Weaknesses in implementing learning implementation plan curriculum are inadequate learning media so that it becomes an obstacle to developing a balance between developing spiritual and social attitudes, curiosity, creativity, cooperation with intellectual and psychomotor abilities.